More about Diamonds - SHUBIN Vladimir Gennadievich (Ученые записки Института Африки Российской академии наук)
Abstract. The article is a rejoinder to the work of Yury S. Skubko, previously published in the Journal of the Institute for African Studies, on Moscow’s relations with De Beers. It is based not only on the available literature but also on the author’s personal experience. The author shows that under the monopoly of this South African company in the field of diamond sales, Soviet organizations, even in the conditions of a South African boycott, were forced to deal with its subordinate structures and the attempts to sideline them were in vain.